2019
DOI: 10.1101/658310
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adaptive and Innate Immune Cell Responses in Tendons and Lymph Nodes After Tendon Injury and Repair

Abstract: Tendon injuries are a common clinical condition with limited treatment options. The cellular components of the innate system, such as neutrophils and macrophages, have been well studied in tendon injuries. However the adaptive immune system, comprised of specialized lymphocytes, plays an important role in orchestrating the healing of numerous tissues but less is known about these cells in tendon healing. To gain a greater understanding of the biological processes that regulate tendon healing, we sought to dete… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…In the patellar tendon, approximately 0.8% of cells are CD146 + (18), which is consistent with the relatively low amount of vasculature within homeostatic adult tendon (3). Previous studies in our laboratory using the synergist ablation model in rats showed that these cells appear to migrate from their niche in the vasculature and proliferate within the neotendon (15).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the patellar tendon, approximately 0.8% of cells are CD146 + (18), which is consistent with the relatively low amount of vasculature within homeostatic adult tendon (3). Previous studies in our laboratory using the synergist ablation model in rats showed that these cells appear to migrate from their niche in the vasculature and proliferate within the neotendon (15).…”
Section: Discussionsupporting
confidence: 81%
“…Tenocytes, or tendon fibroblasts, are the main cell type in tendons and are thought to be responsible for the production, organization, and maintenance of the tendon ECM (2). Tendons are surrounded by an outermost basement membrane called the epitenon, which provides blood and nerve supply to the tendon (1,3). The organization of the ECM allows the tendon to properly transmit forces from muscle to bone and allow for locomotion, and to respond to mechanical stimuli (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Tenocytes, or tendon fibroblasts, are the most abundant cell type in tendon tissue and are responsible for ECM production, hierarchical organization and repair (Gumucio et al 2015). Tendons are also composed of endothelial cells, sensory neurons and tissue resident immune cells, among others, that provide a vascular supply, allow for proper motor control, and support the general growth and homeostatic functions of tendon tissue (Sugg et al 2014;Ackermann et al 2016;Noah et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Biological functions and homeostasis rely on complex cell responses to microenvironmental stimuli. The articulated interplay of immune cells and resident cell population is critical for timely and spatial regulation to achieve proper healing and stimulate regeneration [ 10 ]. Although inflammatory cues are necessary to trigger the repair mechanisms, if perpetuated, pro-inflammatory signals can impair regenerative response and produce a deleterious effect on tendon functionality [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although immune cells are necessary for tendon repair, their persistent activation can result in incomplete resolution of inflammation [ 8 ] and may lead to chronic injury [ 9 ]. Recent studies indicated that the adaptive and innate immune systems work with tissue resident cells to coordinate tissue repair [ 10 ], suggesting that the mechanisms to counteract inflammatory stimuli may be insufficient in natural tendon injury. Consequently, this limited intrinsic response creates new opportunities to investigate the interplay of immune cells and human tendon cells (hTDCs) envisioning new molecular and cellular treatment possibilities.…”
Section: Introductionmentioning
confidence: 99%